Sex allocation, sex ratios and reproduction - Hardy, Ian C.W.; Boulton, Rebecca A. (Elsevier, 2018)
Sex allocation theory provides a powerful framework for understanding a range of reproductive behavior, including the numerical sex ratio of the progeny that parents produce. Starting with evolutionary explanations for why many species have unbiased sex ratios, sex ratio theory has developed to account for the major exceptions and is now extremely detailed and sophisticated, due to an excellent interchange between model development and empirical testing. While sex ratios are a fascinating aspect of behavior in their own right, their study has also improved the general understanding of evolutionary processes and the potential to tackle important medical and ecological problems.